Epidemiology of Status Epilepticus in Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The incidence, etiology, seizure characteristics, and outcome in childhood convulsive status epilepticus (CSE) are reviewed by researchers from Great Ormond Street Hospital for Children, and the Institute of Child Health, London, UK.